PENGARUH METODE SHOW AND TELL TERHADAP KETERAMPILAN BERBICARA SISWA KELAS III SD - Wiranda, Chindy Audry; Affandi, Lalu Hamdian; Setiawan, Heri (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2024)
This study aims to determine whether there is an effect of the Show and Tell method on speaking skills. The type of research used is Quasi Experiment Design Type Non-equivalent Control Group Design. The sampling technique used is purposive sampling. The total number of samples is 62 students. The data analysis in this study used SPSS version 22.0 for windows. The statistical test in this study used a non-parametric test (Mann-Whitney Test). Based on the results, the average value of the experimental class changed, namely from the pre-test value of 55,156 and the posttest value of 66,093. The results of statistical calculation data analysis using the test (Mann Whitney-Test) obtained a significance level of 0.000 <0.05, then Ha is accepted and H0 is rejected. This study shows that there is an effect of the Show and Tell method (showing and telling stories) on the speaking skills of third grade students of SDN 1 SANDIK.